2015
DOI: 10.1515/intag-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of soil column incubation experiments to measure CO2 efflux

Abstract: Accurate measurements of CO2 efflux from soils are essential to understand dynamic changes in soil carbon storage. Column incubation experiments are commonly used to study soil water and solute transport; however, the use of column incubation experiments to study soil CO2 efflux has seldom been reported. In this study, a 150-day greenhouse experiment with two treatments (no-tillage and tillage soils) was conducted to evaluate the applicability of soil column incubation experiments to study CO2 efflux. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The closed chamber method has also been employed in the laboratory where soil cores are extracted from the field and placed in columns with their bases capped (e.g., Jansen 2008;Guo et al 2015;Susilawati et al 2016), with the advantage that environmental conditions can be regulated. During a gas sampling event, a removable bung with two holes (a pressure vent and a sampling port, see Figure 1), is placed on the column through which headspace air can be sampled.…”
Section: Closed Chamber Methods Introductionmentioning
confidence: 99%
“…The closed chamber method has also been employed in the laboratory where soil cores are extracted from the field and placed in columns with their bases capped (e.g., Jansen 2008;Guo et al 2015;Susilawati et al 2016), with the advantage that environmental conditions can be regulated. During a gas sampling event, a removable bung with two holes (a pressure vent and a sampling port, see Figure 1), is placed on the column through which headspace air can be sampled.…”
Section: Closed Chamber Methods Introductionmentioning
confidence: 99%
“…Column was fixed on a tyrofoam base properly insolated to prevent soil water loss and keeping at 60 % of field capacity, which was constantly weighted with water addition when requested. This study was developed in incubation due to the controlled experimental conditions as demonstrated by 15,28 . The setup was left in an open laboratory environment at a controlled temperature (25 °C),…”
Section: Soil and Residues Incubationmentioning
confidence: 99%
“…Column was fixed on a tyrofoam base properly insolated to prevent soil water loss and keeping at 60 % of field capacity, which was constantly weighted with water addition when requested. This study was developed in incubation due to the controlled experimental conditions as demonstrated by 15,28 . The setup was left in an open laboratory environment at a controlled temperature (25 °C), during 73 days of incubation.…”
Section: Soil and Residues Incubationmentioning
confidence: 99%